Genome-wide analysis of the binding of the hox protein ultrabithorax and the hox cofactor homothorax in Drosophila. - Choo, S.W.; White, R.; Russell, S. (PLoS ONE, 2011)
Hox genes encode a family of transcription factors that are key developmental regulators with a highly conserved role in specifying segmental diversity along the metazoan body axis. Although they have been shown to regulate a wide variety of downstream processes, direct transcriptional targets have been difficult to identify and this has been a major obstacle to our understanding of Hox gene function. We report the identification of genome-wide binding sites for the Hox protein Ultrabithorax (Ubx) using a YFP-tagged Drosophila protein-trap line together with chromatin immunoprecipitation and microarray analysis. We identify 1,147 genes bound by Ubx at high confidence in chromatin from the haltere imaginal disc, a prominent site of Ubx function where it specifies haltere versus wing development. The functional relevance of these genes is supported by their overlap with genes differentially expressed between wing and haltere imaginal discs. The Ubx-bound gene set is highly enriched in genes involved in developmental processes and contains both high-level regulators as well as genes involved in more basic cellular functions. Several signalling pathways are highly enriched in the Ubx target gene set and our analysis supports the view that Hox genes regulate many levels of developmental pathways and have targets distributed throughout the gene network. We also performed genome-wide analysis of the binding sites for the Hox cofactor Homothorax (Hth), revealing a striking similarity with the Ubx binding profile. We suggest that these binding profiles may be strongly influenced by chromatin accessibility and provide evidence of a link between Ubx/Hth binding and chromatin state at genes regulated by Polycomb silencing. Overall, we define a set of direct Ubx targets in the haltere imaginal disc and suggest that chromatin accessibility has important implications for Hox target selection and for transcription factor binding in general.